(untitled) (American Journal of Technology and Applied Sciences, 2026)
In this article, the selection of adsorbents with high efficiency in gas drying and their physico-chemical parameters are discussed. Special cleaning processes in order to partially dry moisture and mechanical impurities in natural gas: adsorption in molecular systems; increasing the processing efficiency of solid adsorbent-zeolites is achieved. As a result of scientific research, the renewal of adsorbents has been scientifically based, and directions for the introduction of research have been studied.